The Correlation Between Toll-Like Receptor-5 Gene Polymorphism with Serum Level of Toll–Like Receptor-5 and Interleukin-6 and Interleukin-12 Response to Toxoplasma Gondii in Pregnant Women - Adel Neama Al-Baldawy, Huda Dhaher Al-Marsomy, Inas Ismail Kahleel (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Toxoplasma gondii is an obligate intracellular parasite that can cause variable clinical symptoms or can even be asymptomatic in immunocompetent individuals. The parasite is known to cause congenital diseases, ocular, and miscarriage in pregnant women. Primary infections are dangerous in pregnant women, that occurring usually asymptomatically, especially in the first trimester. Different rates of pregnant women are infected with Toxoplasma gondii in different countries. Primary infections in pregnant women result in transmission of Toxoplasma. gondii through the placenta to the fetus and then in congenital infections, and it is not the only reason for miscarriage, the activity of Toll -like receptors in defense against Toxoplasma gondii infections was observed such as Toll-like receptor5 molecule, and some cytokines (such as IL-6, and IL-12 ), maybe lead to abortion. Several single-nucleotide polymorphisms (SNPs) residing in genes encoding these receptors were reported as significant genetic modifications of Toll- like receptors and correlated with miscarriage. Objectives : Study the correlation of TLR-5 gene polymorphism in pregnant women infected with toxoplasmosis, and study association of TLR-5 polymorphisms with the serum level of TLR-5 and cytokines (IL-6, IL-12) in pregnant women infected with toxoplasmosis. Methods: The present Case-control study was conducted on 100 women, of which fifty pregnant women seropositive (IgG, IgM) for Toxoplasma gondii (Group1), fifty pregnant women seronegative (IgG, IgM) for Toxoplasma gondii (Group2), as a control group, collected in the period from January 2021 to December 2021. All patients were recruited from Obstetrics and Gynecology Department of Balad General Hospital in Balad city / Salah al-Din province/Iraq, and all women participating in the study were under the supervision of a consultant specialist gynecologist and obstetrician. All IgM and IgG seropositive samples for Toxoplasma gondii by rapid test were subjected for detection of IgM and IgG level by ELISA technique to confirm the diagnosis of toxoplasmosis. The serum level of TLR5 and cytokines (IL-6, IL-12) was measurement by ELISA technique. The selected SNPs (rs2072493, rs5744168) in Toll- like receptors 5 were detection by using real-time polymerase chain reaction (RT-PCR). Results: The frequency of the heterozygous genotype (TC) for polymorphism of TLR-5 gene (rs2072493) was higher in pregnant women seropositive 20(40%) than pregnant women seronegative 2(4%) with high significant difference p=0.004 (OR=16, CI=3.48 to 73.4), at allelic level, the frequency of mutant allele (allele C) was in pregnant women seropositive and pregnant women seronegative (20% versus 2%) with high significant difference also p=0.009 (OR=12.25, CI=0. 2.77 to 53.99). The frequency of the heterozygous genotype (GA) was higher in pregnant women seropositive 10(20%) than pregnant women seronegative 4(8%) with no significant difference (p=0.093) (OR=2.87, CI=0.83 to 9.88), at allelic level, in mutant allele (allele A) was in in pregnant women seropositive and pregnant women seronegative (10% versus 4%) with no significant difference p=0.10 also (OR=2.66, CI=0.80 to 8.80). There are increase serum level of TLR-5, IL-6 and IL-12 in pregnant women seropositive. The pregnant women seropositive with rs5744168 show a positive correlation among TLR-5, IL-6 and IL-12. As well as, with rs2072493 show a negative correlation between TLR-5 and IL-6, but, IL-12 was positive correlation in pregnant women seropositive. Conclusion: Overall, there was significant association of toxoplasmosis with mutant allele (allele C), however, the mutant allele (C) of the SNP rs2072493 may be considered as a risk factor for toxoplasmosis and stimulate miscarriage in pregnant women, whereas, the SNP rs5744168 was not considered as a risk factor for toxoplasmosis. There is a significant increase serum soluble level of TLR-5, IL-6 and IL-12 in pregnant women seropositive. Keywords: TLR-5, polymorphism, Toxoplasma gondii, IL-6, IL-12.